French Cycling A Social and Cultural History - Dauncey, Hugh (Contemporary French and Francophone Cultures, 2012)
French Cycling: a Social and Cultural History aims to provide a balanced and detailed analytical survey of the complex leisure activity, sport, and industry that is cycling in France. Identifying key events, practices, stakeholders and institutions in the history of French cycling, the volume presents an interdisciplinary analysis of how cycling has been significant in French society and culture since the late Nineteenth century. Based on a very wide range of primary and secondary sources, the volume aims to present in clear language an explanation of the varied significance of cycling in France over the last hundred years.